Life Goals Matter to Happiness: A Revision of Set-Point Theory - Bruce Headey (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
Using data from the long-running German Socio-Economic Panel Survey (SOEP), this paper provides evidence that life goals matter substantially to subjective well-being (SWB). Nonzero sum goals, which include commitment to family, friends and social and political involvement, promote life satisfaction. Zero sum goals, including commitment to career success and material gains, appear detrimental to life satisfaction. Finding that conscious life goals matter can potentially make an important contribution to SWB theory. The most widely accepted theory – set-point or dynamic equilibrium theory – essentially claims that set-points are near-automatic consequences of hereditary characteristics, including personality traits. Life goals play no role in these theories and major life events are viewed as having only a transitory effect. The SOEP panel data show that, over a 15-20 year period, non-trivial minorities record substantial changes in their set-points. This paper shows linkages between these changes and (a) the personality traits of extraversion, neuroticism and internal locus of control and (b) choice of life goals.
Keywords: 330